The Effect of Using YouTube Learning Videos on Mathematics Learning Outcomes in Whole Numbers Material for Second Grade Students at SDN 16 Sitiung - Asmara, Dwi Novri; Novitasari, Ana; Jannah, Miftahul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study is based on the low learning outcomes of students in mathematics subjects in grade II of SD Negeri 16 Sitiung. The low learning outcomes of students are due to students not paying attention during the learning process, causing many students' scores to still be below the KKTP Education Level Framework that must be achieved by students in mathematics subjects, which is 70. This study aims to determine the significant effect of implementing learning videos on student learning outcomes in mathematics subjects in grade II of SD Negeri 16 Sitiung. The type of research used is experimental. In the research used is pre-experimental designs (non-designs). In this study using One-Group Pretest-Posttest Designs. The stages of this research are preparation, implementation and completion. And the data analysis techniques that researchers do are normality tests and parametric tests. The results of this study show that the pretest results have an average value of 62.895 while the posttest value has an average of 83.947. In the normality test for pretest data, the data is normally distributed and for posttest data, it is normally distributed. Because the data is normally distributed, a parametric hypothesis test is carried out. With the results of the parametric test using paired sample tests SPSS 25, the significance result is 0.000. Because the significance value of 0.000 <0.5, it can be concluded that Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence in the application of learning videos on the learning outcomes of students in the mathematics subject of class II of SD Negeri 16 Sitiung.